Home Kredit Integration System and Vehicle Insurance Policy Simas Insurtech at Sinar Mas Insurance - Jemi Yosua Laoere (International Journal of Information Technology and Business, 2024)
Web service API is meant for each platform to be connected and can be used for personal, group, or company needs. Web service API in the insurance world is used for insured parties to get their policy numbers and payment details for insurance purposes both for self-insurance and the property of the insured. By using a primary data collection method that is directly from the source, by using existing parameters in the procedure that was made previously to be able to get a valid policy number and is used by the insured as a form of cooperation with the Sinar Mas Insurance company. The results of the analysis are the number of policies that have been processed, will be used for the insured to make insurance claims on the insurance. This API has been made which aims to facilitate interaction between application platforms both web-based or mobile in data retrieval without regard to the platform used so that the activity of exchanging data between applications can run properly.